The Effect of Working Environment and Motivation towards Labors’ Performance: A Case Study in Aceh at PT Pupuk Iskandar Muda - Iskandar Hasanuddin; Mohd. Iqbal; Suparno .; Raja Arifin Ghazilla; Friesca Erwan (Graduate Program of Syiah Kuala University, 2019)
This study aims to analyze the effect of the working environment and motivation towards the performance of labors at the packaging department of urea fertilizer in PT. Pupuk Iskandar Muda, Lhokseumawe, Aceh, Indonesia. This study employs the census sample selection method and involves 35 labors at the packaging department in the company. The research variables consist of independent variables (i.e. physical and psychosocial working environment, work motivation, and supporting working tools) and dependent variables (i.e. labors’ performance). Based on data analysis that uses double regression (linear), it shows that the relationship between the independent variables towards the dependent variable is with R square value 46.8%. This circumstance proves that proper physical working environment that provides comfortable and safety procedures to the labors increases their performance. Moreover, the results from the regression coefficient also show a significant effect of the physical working environment, psychosocial working environment, work motivation, and supporting working tools towards the labors’ performance.